Long‐term prognostic value of combined free triiodothyronine and late gadolinium enhancement in nonischemic dilated cardiomyopathy. Issue 1 (23rd January 2018) - Zhang, Kuo; Wang, Wenyao; Zhao, Shihua; Katz, Stuart D.; Iervasi, Giorgio; Gerdes, A. Martin; Tang, Yi‐Da
Abstract : Background: Thyroid dysfunction and myocardial fibrosis are both associated with cardiovascular events in patients with dilated cardiomyopathy (DCM). Hypothesis: The combination of thyroid hormone (TH) and myocardial fibrosis (detected by late gadolinium enhancement [LGE]) is an independent and incremental predictor of adverse events in DCM. Methods: We consecutively enrolled 220 idiopathic DCM patients with thyroid function and LGE assessment at Fuwai Hospital (China) from January 2010 to October 2011 and followed up through December 2015. Patients were divided into 4 groups according to the presence or absence of LGE and FT3 value (median level of 2.79 pg/mL): LGE‐positive + FT3 < 2.79 pg/mL, LGE‐positive + FT3 ≥ 2.79 pg/mL, LGE‐negative + FT3 < 2.79 pg/mL, and LGE‐negative + FT3 ≥ 2.79 pg/mL. Results: During a median follow‐up of 61 months, 56 patients (25.5%) died, with 27/56 (48.2%), 8/45 (17.8%), 12/54 (22.2%), and 9/65 (13.8%) among 4 groups ( P = 0.009), respectively. Multivariable Cox regression analysis identified LGE‐positive and FT3 < 2.79 pg/mL as a significant independent predictor of all‐cause mortality (hazard ratio: 2.893, 95% confidence interval: 1.323‐6.326, P = 0.008). Combining the predictive value of FT3 and LGE status significantly improved risk reclassification for all‐cause mortality, as indicated by the net reclassification improvement (0.28; P = 0.005) and integrated discrimination improvement (0.058; P = 0.001). Conclusions: The findings suggest that the combination of FT3 and LGE yielded a more accurate predictive value for long‐term prognosis in patients with DCM, which may improve patient selection for intensive interventions.